Selma and the Liuzzo murder trials : the first modern civil rights convictions - Turner, James P. (University of Michigan Press, 2018)
In 1965 the drive for black voting rights in the south culminated in the epic Selma to Montgomery Freedom March. After brutal state police beatings stunned the nation on "Bloody Sunday," troops under federal court order lined the route as the march finally made its way to the State Capitol and a triumphant address by Dr. Martin Luther King, Jr. But within hours klan terror struck, claiming the life of one of the marchers, Viola Liuzzo, a Detroit mother of five. Turner offers an insider's view of the three trials that took place over the following nine months--which finally resulted in the conviction of the killers. Despite eyewitness testimony by an FBI informant who was riding in the car with the killers, two all-white state juries refused to convict. It took a team of Civil Rights Division lawyers, led by the legendary John Doar, to produce the landmark jury verdict that klansmen were no longer above the law. This is must reading today, as the voting rights won in Selma come under renewed attack.